2022
DOI: 10.1182/bloodadvances.2021005017
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation accelerates BCR-ABL1+ B-ALL development through upregulation of AID

Abstract: Inflammation contributes to the initiation and disease progression of several lymphoid malignancies. BCR-ABL1-positive B-cell acute lymphoblastic leukemia (BCR-ABL1+ B-ALL) is triggered by the malignant cloning of immature B cells promoted by the BCR-ABL1 fusion gene. However, it is unclear whether the mechanism driving the disease progression of BCR-ABL1+ B-ALL involves inflammatory stimulation. Here, we evaluate BCR-ABL1+ B-ALL cells’ response to inflammatory stimuli lipopolysaccharide (LPS) in vitro and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…AID expression has been associated with blast crisis progression in CML and increases leukemogenesis in BCR-ABL + B-ALL ( 133 ). It has been recently investigated that inflammation contributes enhanced expression AID through NFκB pathway and further increases malignancy in BCR-ABL + B-ALL ( 134 ). BCR-ABL tyrosine kinase inhibitors like imatinib mesylate was the first drug approved for CML.…”
Section: Inflammation In Myeloid Malignanciesmentioning
confidence: 99%
“…AID expression has been associated with blast crisis progression in CML and increases leukemogenesis in BCR-ABL + B-ALL ( 133 ). It has been recently investigated that inflammation contributes enhanced expression AID through NFκB pathway and further increases malignancy in BCR-ABL + B-ALL ( 134 ). BCR-ABL tyrosine kinase inhibitors like imatinib mesylate was the first drug approved for CML.…”
Section: Inflammation In Myeloid Malignanciesmentioning
confidence: 99%
“…Interestingly, in contrast to RAG2, AID was found to be also upregulated by environmental factors, like repeated exposure to inflammatory stimuli, paralleling chronic infections in childhood [13,22,25,27]. Recent studies also describe a depleted microbiome as an accelerator of ALL development, while metabolites of a healthy microbiome prevented leukemia through AID inhibition [58][59][60].…”
Section: Revised Risk Index Based On Primary Aberrations Characterize...mentioning
confidence: 99%
“…AID was documented to be a driver of oncogenic mutations in lymphomas [23,24]. However, recent studies have shown that aberrant activation of AID by infectious signals may also accelerate mutagenic processes leading to childhood ALL [13,[25][26][27]. The abovepresented mutational mechanisms have been well described in pediatric ALL, but the data are insufficient for adult ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines are essential for BM niche homeostasis, and the first studies on B-ALL reported a higher expression of these molecules when compared with healthy BM samples, suggesting an autocrine/paracrine regulation of leukemic cells and cytokines 22 . More recently, studies have demonstrated that inflammation can drive progression of BCR-ABL1 B-ALL 23 . The composition and the contribution of the inflammatory microenvironment in T-ALL still remains poorly explored.…”
Section: Introductionmentioning
confidence: 99%